SYNTHESIS OF CARBON NANOTUBES WITH NI-TI CATALYST - Ayaganov, Zh.E.; Gabdullin, M.T.; Batryshev, D.G.; Ramazanov, T.S.; Guseinov, N.R.; Baughman3, Ray (Academic Scientific Journal of Computer Science, 2020)
Carbon nanotubes have been of interest to the scientists for about 30 years due to their unique properties. Their use as a material for creating flexible conductive coatings, supercapacitors, batteries and solar cells is promising because of their excellent mechanical and electrical properties, as well as high electrochemical stability. In this paper, we consider one of the methods for the synthesis of carbon nanotubes on a Ni-Ti bimetallic catalyst on a silicon substrate. The effect of the thickness of the catalytic layer and the synthesis temperature on the quality of the obtained samples was studied. The synthesis was carried out by the CVD method as the most convenient technique with the possibility of a large yield of the final product. The obtained samples were studied by scanning electron microscopy and Raman spectroscopy. It was found that with an increase in the synthesis temperature and a decrease in the thickness of the catalytic layer, the crystallinity of the structure improves the number of defects in the structure decreases and structural ordering increases. The use of a catalyst and an adhesive metal layer, which was a barrier between the catalyst and the substrate, shows good results in improving the quality of the synthesis of nanotubes.